A comprehensive study on using new hydrogen-natural gas and ammonia-natural gas blends for better performance - Ishaq, H.; Dincer, I. (ELSEVIER SCI LTD, 2020)
This study presents a novel configuration using the hydrogen-natural gas and ammonia-natural gas blends for practical applications and investigates the system performance comprehensively. Natural gas is blended with hydrogen and ammonia to investigate performance improvement. Wind energy source is employed to the proposed configuration for power generation using wind turbines. The power generated by the wind turbine is employed to the proton exchange membrane (PEM) electmlyser for hydrogen production. A part of hydrogen is employed to the PEM fuel cell for power production. The proposed system is used to investigate the effect of hydrogen and ammonia blends with natural gas to achieve better performance. In order to investigate the H-2-CH4 blends, a part of the produced hydrogen is supplied to the mixing chamber from the hydrogen storage tank while ammonia input is supplied to the mixing chamber to improve the performance under NH3-CH 4 blends. The results revealed that the combustion energy and exergy efficiencies increase from 84.8% to 94.8% and 62.5%-70.2% respectively and the overall energetic and exergetic efficiencies increase from 37.4% to 40.3% and 36.8%-39.8% respectively with hydrogen addition from 0 to 20%. In the case of ammonia-natural gas blends, the combustion energy and exergy efficiencies increase from 84.8% to 92.9% and 58.9%-64.4% respectively and overall energetic and exergetic efficiencies increase from 37.4% to 39.1% and 36.8%-38.5% respectively.
Keywords: Natural gas; Hydrogen; Ammonia; Renewable energy; Wind energy; Exergy; Efficiency; ENERGY; COMBUSTION; OPTIMIZATION; DESIGN; Energy & Fuels; Engineering